HUBUNGAN KECEMASAN DAN MOTIVASI BERTANDING TERHADAP PERFORMANCE ATLET BOLA VOLI KLUB PUTRI ANGIN KUANTAN SINGINGI - Rahayu, Tika; Sulastio, Agus; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The issues experienced by the female volleyball athletes in KuantanSingingi include their inability to perform optimally due to anxiety and a decline incompetitive motivation. This is caused by their inability to manage anxiety at a stablelevel, which stems from low playing motivation. The author conducted research on thisissue with the hope that the findings could provide one of the best solutions to theproblem. During observations, the researcher identified that the volleyball athletes inKuantan Singingi struggled to deliver their best performance due to anxiety anddecreased competitive motivation. The objective of this study is to determine therelationship between anxiety and competitive motivation on the performance of femalevolleyball athletes from the Putri Angin Club in Kuantan Singingi. The type of researchemployed in this study is correlational. The population and sample consist of 14 players from the Putri Angin Club. The test instruments used are (1) an Anxiety Questionnaire and (2) a Competitive Motivation Questionnaire, both of which assess the athletes' performance in executing basic volleyball techniques. The data analysis utilized is the R-value test. The findings of the research indicate: (1) There is a relationship between anxiety and the performance of female volleyball athletes in the Putri Angin Club, Kuantan Singingi, with a calculated rrr-value (rrr-hitung) of 0.631 ≥ rrr-table (rrr-tabel) of 0.532. (2) There is a relationship between competitive motivation and the performance of female volleyball athletes in the Putri Angin Club, Kuantan Singingi, with a calculated rrr-value (rrr-hitung) of 0.671 ≥ rrr-table (rrr-tabel) of 0.532. (3) There is a relationship between both anxiety and competitive motivation and the performance of female volleyball athletes in the Putri Angin Club, Kuantan Singingi, with a calculated rrr-value (rrr-hitung) of 0.687 ≥ rrr-table (rrr-tabel) of 0.532.Keywords: Anxiety, Competitive Motivation, Athlete Performance